2021
DOI: 10.1186/s13223-021-00551-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and demographic pattern of chronic granulomatous disease (CGD) from a multicenter perspective: Malaysia’s experience over 26 years

Abstract: Background A retrospective review of clinical manifestations and demographic pattern of patients diagnosed as chronic granulomatous disease (CGD) from 7 hospitals in Malaysia. An analysis of the available database would establish clinical characteristics, diagnoses and outcome including microbiologic pattern. Studying the demography allows us to document the occurrence of CGD amongst multiethnic groups and its geographical distribution for Malaysia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Comparable with other studies, Aspergillus species was the prevalent fungal microorganism detected in our cohort (16,18,20,21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparable with other studies, Aspergillus species was the prevalent fungal microorganism detected in our cohort (16,18,20,21).…”
Section: Discussionsupporting
confidence: 81%
“…This is explained by the high level of consanguinity in UAE like other countries within the MENA region, such as Oman (5), Saudi Arabia (6), Turkey (12), Iran (13) and Egypt (15). Although X-linked CGD is the most common form of the disease in the United kingdom, Latin America, Mexico, and USA (2,10,11,16), it was only observed in one patient in our cohort.…”
Section: Discussionmentioning
confidence: 64%
“…Uniquely in SEA countries, the disease phenotype of PID is rather unusual as its initial presentations are not commonly described in classical literature ( 10 ). Studies have reported higher incidence of Mycobacterium tuberculosis , Mycobacterium bovis , Chromobacteriumviolaceum, Burkholderiapseudomallei and Penicillium marneffei , which are endemic in SEA countries ( 10 , 11 ). Therefore, in cases where live vaccines such as Bacillus Calmette-Guerin (BCG) are administered to severely immunodeficient infants in SEA countries, they may experience complications, often leading to death with a high mortality rate of 43.5% ( 10 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some countries are equipped with up-to-date national registries (14 countries), while many lack registries altogether (38 countries). Some countries such as Malaysia ( 36 ), Vietnam and Algeria have registries based on data from a few medical centres, while others, such as South Korea, have a PID registry connected to only one medical centre. In contrast, in large countries with many medical centres treating PID patients such as Canada and the United States of America, finding ways to centralise the registries is a huge challenge that, if solved, could greatly benefit the PID community.…”
Section: Resultsmentioning
confidence: 99%